2015
DOI: 10.1002/hed.23881
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of positron emission tomography and positron emission tomography-CT in the detection of differentiated thyroid cancer recurrence with negative131I whole-body scan results: A meta-analysis

Abstract: (18) Fluorodeoxyglucose (FDG)-PET and PET-CT are highly accurate diagnostics tools for DTC recurrence in patients who present a negative whole-body scintigraphy and could impact the clinical and therapeutic management of DTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 52 publications
2
22
0
4
Order By: Relevance
“…(20). Similar data, reported by Caetano et al in 2015, was obtained from a meta-analysis evaluating the sensitivity and specificity of FDG-PET/CT in the detection of DTC recurrences to be 93 and 81% respectively (21). The sensitivity of FDG-PET/CT in our study was relatively low probably because some enrolled patients showed only a slight increase in serum Tg level.…”
Section: Discussionsupporting
confidence: 58%
“…(20). Similar data, reported by Caetano et al in 2015, was obtained from a meta-analysis evaluating the sensitivity and specificity of FDG-PET/CT in the detection of DTC recurrences to be 93 and 81% respectively (21). The sensitivity of FDG-PET/CT in our study was relatively low probably because some enrolled patients showed only a slight increase in serum Tg level.…”
Section: Discussionsupporting
confidence: 58%
“…For distant metastases, particularly of the lung and bones, FDG-PET/CT reaches both sensitivity and specificity up to 1.00 [14, 15, 19]. Nonetheless, the sensitivity and specificity of FDG-PET/CT for detecting locally recurrent or metastatic TC is still relatively low and ranges between 0.46 to 1.00 and 0.66 to 1.00, respectively [5, 12, 17]. Furthermore, recurrent, residual, or metastatic tissue does not always accumulate 18 FDG, and thus remains undetectable by FDG-PET/CT.…”
Section: Introductionmentioning
confidence: 99%
“…In case of lower thyroglobulin levels, 18 FDG PET/CT can be false negative due to the presence of microscopic disease. The specificities of 18 FDG PET alone and PET/CT methods were similar (81-84%) (99,100). This is due to the fact that inflammation also increases FDG uptake.…”
Section: F-fluorodeoxyglucose Positron Emission Tomographymentioning
confidence: 69%
“…The combination of functional and morphologic data furnished by this approach substantially improves the anatomic localization of lesions. Two meta-analyses analyzed the diagnostic performances of 18 FDG PET and 18 FDG PET/CT for the detection of persistent/recurrent DTC in patients with detectable Tg and no evidence of RAI uptake (99,100). In both cases, the patient-based sensitivity of PET/CT was appreciably higher than PET alone (93-94% vs 83-84% for 18 FDG PET).…”
Section: F-fluorodeoxyglucose Positron Emission Tomographymentioning
confidence: 99%